PENGARUH BERBAGAI PEMBIAYAAN TERHADAP PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA - Kartika Fatharani; Achmad Fauzi; Indah Muliasari (Yayasan Education and Social Center, 2023)
Financing is a fund provided by Islamic banking to assist customers in financing what they need under certain conditions and benefit both parties. Financing in Islamic banking consists of sale and purchase financing, profit sharing financing and lease financing. This research was conducted at the Sharia Rural Bank in Indonesia. The purpose of this study is to find out how financing at Islamic people's financing banks in Indonesia affects their profitability. The data used are financial statements obtained from the website of the Islamic people's credit bank or the website of the Financial Services Authority in Indonesia. The method used in this study is a quantitative descriptive method, which discusses problems by collecting data, deciphering, calculating, and explaining the effect of various financing on Sharia Rural Bank in Indonesia. Based on the results of the study, profitability in Islamic people's financing banks in Indonesia in 2021-2022 is insignificantlysignificantly influenced by various financings